2013
DOI: 10.1002/dta.1522
|View full text |Cite
|
Sign up to set email alerts
|

Determination of 4‐bromo‐2,5‐dimethoxy‐N‐[(2‐methoxyphenyl)methyl]‐benzeneethanamine (25B‐NBOMe) in serum and urine by high performance liquid chromatography with tandem mass spectrometry in a case of severe intoxication

Abstract: We present a case of 4-bromo-2,5-dimethoxy-N-[(2-methoxyphenyl)methyl]-benzeneethanamine (25B-NBOMe), an N-benzyl phenethylamines derivative, intoxication and a high performance liquid chromatography with tandem mass spectrometry (HPLC-MS/MS) method for detection and quantification of 25B-NBOMe.A 19-year-old male was found unresponsive with generalized grand mal seizure activity. On the second day of hospitalization, a friend admitted that the patient used ‘some unknown drug’ called 25B. Serum and urine collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 19 publications
1
40
0
Order By: Relevance
“…Validated HPLC/MS/MS methods have been published for detection and quantification of 25I-NBOMe in serum 13,38 , urine 38 and numerous postmortem fluids and solid tissues 14 . Additionally, validated quantification methods are available for 25C-NBOMe in serum 38 and urine 20,39 , 25B-NBOMe in serum 15 and urine 15,20 and an additional six NBOMe derivatives in urine 39 . Serum specimens for NBOMe testing should be collected in the classic red top or gray top blood tubes.…”
Section: Discussionmentioning
confidence: 99%
“…Validated HPLC/MS/MS methods have been published for detection and quantification of 25I-NBOMe in serum 13,38 , urine 38 and numerous postmortem fluids and solid tissues 14 . Additionally, validated quantification methods are available for 25C-NBOMe in serum 38 and urine 20,39 , 25B-NBOMe in serum 15 and urine 15,20 and an additional six NBOMe derivatives in urine 39 . Serum specimens for NBOMe testing should be collected in the classic red top or gray top blood tubes.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest are N-2-methoxybenzyl-phenethylamines (NBOMe drugs), which are novel and reportedly very potent hallucinogens that have been increasingly used recreationally (Forrester, 2014;Hill et al, 2013;Ninnemann and Stuart, 2013;Rose et al, 2013;Walterscheid et al, 2014;Wood et al, 2015;Zuba, 2012), with additional potential use as radiotracers (Ettrup et al, 2011;Ettrup et al, 2010). Recreationally used NBOMe drugs include 25I-NBOMe, 25C-NBOMe, 25B-NBOMe, and 25D-MBOMe (Armenian and Gerona, 2014;Poklis et al, 2014;Rose et al, 2013), which are derivatives of 2,5-dimethoxy-4-substituted phenethylamines (2C drugs; Dean et al, 2013;Hill and Thomas, 2011;Shulgin and Shulgin, 1991). N-2-methoxybenzyl substitution enhances the potency of 2C drugs at serotonergic 5-hydroxytryptamine-2A (5-HT 2A ) receptors, resulting in exceptionally potent 5-HT 2A receptor agonists (Braden et al, 2006;Heim, 2004;Nichols et al, 2015) with strong hallucinogenic properties in animals and humans (Halberstadt and Geyer, 2014;Srisuma et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…M a n u s c r i p t EMCDDA, 2014c;Forrester, 2014;Grautoff and Kähler, 2014;Hill et al, 2013a;Laskowski et al, 2015;Nikolaou et al, 2015;Poklis et al, 2014b;Rose et al, 2013;Stellpflug et al, 2014;Tang et al, 2014b;Wood et al, 2015). Analysis of acute intoxication with NBOMe and 2C-X drugs reported to the National Poison Data System USA demonstrated that there had been higher incidence of hallucinations/delusions, single episode seizures and benzodiazepine administration in NBOMe exposures that those in 2C exposures (Srisuma et al, 2015).…”
mentioning
confidence: 96%